Pengaruh Kualitas Pelayanan, Brand Image, Dan Atmosfer Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Intervening (Studi Kasus Pada Konsumen Cafe Kosulas Lawang) - Beny Pradana; Nur Hajati; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT The purpose of this study is to determine the effect of Service Quality, Brand Image, and Atmosphere on Customer Loyalty with Consumer Satisfaction as an intervening variable. This type of research is quantitative research. The population in this study are consumers who have come to Café Kosulas Lawang for one month. This study uses a path analysis model method. The results of this study indicate that service quality and brand image have a direct effect on customer satisfaction, the atmosphere has no direct effect on customer satisfaction. Consumer satisfaction has a direct effect on consumer loyalty. Service quality and brand image have an indirect effect on consumer loyalty through customer satisfaction, while the atmosphere has a direct effect on consumer loyalty without going through customer satisfaction.